If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 25 = 43 Reorder the terms: 25 + 9x = 43 Solving 25 + 9x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 9x = 43 + -25 Combine like terms: 25 + -25 = 0 0 + 9x = 43 + -25 9x = 43 + -25 Combine like terms: 43 + -25 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| -15+5(2)=-5y | | -2(2x-6)=32 | | 6x^2=x-24 | | 7x-10+x+4=90 | | -4=(-2) | | -4=(0) | | 7x-10+x+4=180 | | 24x-3y-18=0 | | -2=(2) | | 2pq+pq= | | 6*(x+2)= | | (-14)+3= | | 2+3y=19 | | -4=2 | | 4+x=-10 | | 4x+21+11x+9=180 | | 9g-13=2g | | 7-15=-(3-8) | | 3n+7=4 | | 7x-10=x+4 | | y+2=-3(-2)+8 | | c+6=-3 | | y+2=-3(0)+8 | | -3.1+x=-2.1 | | 6a-3=2 | | y+2=-3(2)+8 | | -3x(2x-3)=-5x+5 | | 6n+3=-2n+12 | | 6+3=3-3y | | -6(-2)+5=y | | 13+a=11 | | 125n^3-50n^2+100n-40= |